Atomic force microscopy, deformation-recovery and numerical study of wheat dough - Mohammed, Mohd Afandi P.; Wakisaka, Minato (Elsevier B.V., 2024)
Experimental and numerical modelling work related to microstructure and deformation of starch, gluten and wheat dough was presented. Atomic force microscopy analyses through force spectroscopy on starch samples showed elastic behaviour of both dried and reconstituted wet starch granules, where wet starch was shown to be more cohesive than dried starch. Deformation-recovery test over time under compression mode showed almost complete recovery to original sample height of gluten, whereas only a slight recovery was observed for dough. Finite element modelling was then commenced to simulate gluten deformation-recovery and starch-gluten dough deformation. The gluten geometry used for the starch-gluten dough model was obtained from cryo-SEM image from the previous work before the starch geometry was then included. The interface between the starch and gluten model was defined using viscoelastic cohesive zone elements. The modelling results suggested significant influence of gluten cellular structure towards starch-gluten dough integrity. In addition, the results from the current work further supported the previous report of the starch-gluten interfacial behaviour using viscoelastic cohesive zone model.